The Body of the Mother in Contemporary Black Women Narratives: (Re)Writing immanence towards transcendence - Cristina M. T. Stevens (Ilha do Desterro)
Articulating class, gender and race issues, we analyze black motherhood in novels by contemporary black women writers, the harsh reality of this experience under slavery, colonization and its consequences in contemporary society. hey expose the bodily aspects of labor, in deep contrast with the patriarchal, idealized images of western motherhood; in doing so, however, they reject its characterization as a purely immanent process which deines and entraps women’s body in utterly distorted, essentialist terms.